Making Your Own Weather: Self-Reliance and Working for Resettlement Among Sudanese Refugee Men in Amman, Jordan - Jordan, Zoë (Refuge: Canada's Journal on Refugees, 2024)
In recent years, refugee response in Jordan has centred on self-reliance, aiming to support individuals in displacement and contain further movement. However, non-Syrian refugees have been largely overlooked. This article explores the relationship between self-reliance and resettlement for Sudanese refugee men in Amman. Drawing on conceptualizations of work beyond paid labour, I show how refugees have pursued resettlement through relational, emotional, physical, and administrative work. I contribute to understandings of how forced migrants work towards long-term solutions to displacement and add to the limited literature on Sudanese displacement in Jordan.